2011
DOI: 10.1007/s10528-011-9485-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure of the Carnivorous Plant Pinguicula moranensis (Lentibulariaceae) on the Transvolcanic Mexican Belt

Abstract: Most species of Pinguicula present a montane distribution with populations located at high altitudes. In this context, we proposed that populations of Pinguicula species could be genetically differentiated even at a local scale. This study supported that prediction, as a RAPD-based analysis of molecular variance revealed a high degree of genetic structure (Φ (st) = 0.157, P = 0.001) and low gene flow (Nm = 1.0) among four central populations of Pinguicula moranensis in Mexico, with a maximum geographic separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 59 publications
2
5
0
Order By: Relevance
“…We studied several components of the interaction between P. moranensis and its pollinators in order to contribute to knowledge of the reproductive ecology of carnivorous plants. Given the pattern of genetic variation observed in P. moranensis , which is compatible with that expected for outcrossed species (Alcalá & Domínguez ), we predicted that P. moranensis would perform as a cross‐pollinated species. The evidence found supported this prediction; however, we mainly discuss implications of the patchy distribution of these plants and behaviour of pollinators for gene movement in this species.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…We studied several components of the interaction between P. moranensis and its pollinators in order to contribute to knowledge of the reproductive ecology of carnivorous plants. Given the pattern of genetic variation observed in P. moranensis , which is compatible with that expected for outcrossed species (Alcalá & Domínguez ), we predicted that P. moranensis would perform as a cross‐pollinated species. The evidence found supported this prediction; however, we mainly discuss implications of the patchy distribution of these plants and behaviour of pollinators for gene movement in this species.…”
Section: Discussionsupporting
confidence: 70%
“…). The pattern in which genetic variation is partitioned in P. moranensis (Alcalá & Domínguez ) corresponds to that expected from a predominantly outcrossed species (Nybom ). The reproductive organs are located at the flower throat and, while stamens and style are thick and short, the two functional anthers are located just below ( ca .…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Prolonged periods of flower longevity also have been reported for other Pinguicula species (Molau ; García et al . ; Zamora ; Alcalá & Domínguez ). It is possible that the flower longevity noted in our study could be a reproductive strategy to increase pollinator visitation and fertilization of ovules (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Flower longevity also was assessed for each of the three Pinguicula species, as several studies have reported flower longevity for other Pinguicula species (Molau 1993;García et al 1994;Zamora 1999;Alcalá & Domínguez 2012). In addition, in 2013 and 2014 it was noted that a corolla would fall from the plant a few days after it was successfully hand-pollinated.…”
Section: Reproductive Ecologymentioning
confidence: 99%